Pendidikan Kesetaraan Gender dalam Perspektif Al-Qur’an: Analisis Pendekatan Library Research - Ami Syadila Sipayung (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
The purpose of writing this scientific paper is to find out what is meant by gender equality education and gender equality education in the perspective of the Qur’an. This writing uses literature study, namely writing whose subject is in the form of library literature, using primary sources in books written by Nasaruddin Umar. The definition of gender equality education is an effort in which all human beings, both men and women are free to develop their personal abilities and make choices without being limited by stereotypes, rigid gender roles. This does not mean that women and men must always be equal, but that their rights, responsibilities and opportunities are not affected by whether they are born male or female. Gender equality education in the perspective of the Qur’an, Nasaruddin Umar revealed that there are principles of gender equality set forth in the Qur’an, namely: men and women as servants of Allah, men and women as caliphs on earth, men -men and women receive the primordial agreement, Adam Eve is actively involved in the cosmic drama, men and women have the potential to achieve achievements as human beings.